WIDESPREAD OF STRAY DOGS: METHODS FOR SOLVING THE PROBLEM IN CERTAIN REGIONS OF BOSNIA AND HERZEGOVINA - Katica, Muhamed; Gradascevic, Nedzad; Hadzimusic, Nejra; Obradovic, Zarema; Mujkanovic, Ramo; Mestric, Esad; Coloman, Senad; Dupovac, Muhamed (International Journal of Research -GRANTHAALAYAH, 2017)
Stray dogs are the ones not microchipped, which live across the streets and other public surfaces unattended, and so represent a serious public-health problem. Lack of human support for the stray dogs causes a range of problems - from territorial status to ensuring food. Such conditions force them to activate a self-preservation mechanism and return to natural behavioral patterns. Regarding the fact that several thousands of stray dogs were recorded in observed regions of Bosnia and Herzegovina in the period from 2008 – 2009, it was obvious that such conditions could endanger the health of both humans and domestic animals. The problem in Bosnia and Herzegovina attempted to be solved using various approaches during the period from 1996 – 2009. Some solutions were: using hygiene services of public utility companies in some places, or establishing dog shelters. The third solution for the problem was the employment of hunting associations and their active participation for reducing the number of stray dogs. Minimization of large number of stray dogs required number of measures and activities such as aplicable legal framework, education for dog owners, neutering of dogs, building shelters, euthanasia of ill and agressive dogs and permanent hosting of dogs.